Enhancing IANB success: panoramic guidance for locating mandibular foramen - Zubair, Muhammad; Zahid Mehmood Khan; Ahmad Shah Khan; Jawad Ali Shah; Nadeem Ahmad Rana (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the spatial relationship of the mandibular foramen with occlusal plane and the anterior border of the ramus using orthopantomograms. Method: The cross-sectional, observational retrospective study was conducted at the Department of Operative Dentistry and Endodontics, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from June 1 to December 1, 2023, and comprised panoramic radiographs containing both mandibular molars of patients aged 18-65 years. Reference points included the anterior border of the ramus, the most anterior-superior point of the mandibular foramen, and the occlusal plane. Distances from the mandibular foramen to the occlusal plane and the anterior border of the ramus were recorded on both sides. Comparisons were made with respect to age and gender. Data was analysed using SPSS 23. Results: Of the 201 patients, 122(60.7%) were males and 79(39.3%) were females. The overall mean age was 40.04±12.76 years (rang: 18-65 years). Based on the panoramic radiographs, the recommended site for inferior alveolar nerve block was approximately 3.88mm above the occlusal plane and 19.35mm from the anterior margin of the ramus. The maximum and minimum distances from the mandibular foramen to the occlusal plane were 9.70mm and -3.11mm, respectively. The mean distance between mandibular foramen and the occlusal plane on the right was 4.01±1.712mm, and it was 3.75±1.676mm of the left. The mean distance from mandibular foramen to ramus on the right was 19.31±2.336mm, while it was 19.38±2.424mm on the left. Conclusion: Panoramic radiographic guidance could improve the success rate of the inferior alveolar nerve block by precisely locating the mandibular foramen in relation to key anatomical landmarks. Key Words: Mandibular foramen, MF, Occlusal plane, OP, Inferior alveolar nerve block, IANB.